Atherosclerotic Burden and Arterial Stiffness are Not Increased in Patients with Milder Forms of Primary Aldosteronism Compared to Patients with Essential Hypertension - Lottspeich, Christian; Köhler, Anton; Czihal, Michael; Heinrich, Daniel A.; Schneider, Holger; Handgriff, Laura; Reincke, Martin; Adolf, Christian (Hormone and Metabolic Research, 2021)
Patients with primary aldosteronism (PA) are at increased cardiovascular risk, compared to patients with essential hypertension (EH). Cardiovascular damage could depend on PA phenotype, potentially being lower in milder forms of PA. Our aim was to assess atherosclerotic burden and arterial stiffness in 88 prospectively recruited patients, including 44 patients with mild PA and EH respectively. All patients underwent a structured study program, including measurements of ankle-brachial index, oscillometric measurement of central pulse wave velocity (cPWV) and vascular ultrasound examination of the supraaortic arteries, the abdominal aorta, and the femoropopliteal arteries. A plaque score was calculated to estimate atherosclerotic burden for each patient. This is a prospective case-control study set at a tertiary care hospital. Patients with PA and EH matched well for age, gender, blood pressure, BMI, and cardiovascular risk factors such as diabetes mellitus and smoking status. Common carotid intima-media thickness (0.77 vs. 0.75 mm; p=0.997) and cPWV (7.2 vs. 7.1 m/s; p=0.372) were comparable between patients with PA and EH. The atherosclerotic burden, as expressed by the plaque score, did not differ between the two groups (p=0.159). However, after initiation of treatment cPWV was significantly decreased in patients with PA (p=0.017). This study shows that subclinical atherosclerotic burden and arterial stiffness in patients with milder forms of PA is comparable to patients with EH. Nevertheless, specific treatment for PA significantly improved cPWV, which argues for a more liberal use of mineralocorticoid receptor antagonists in patients with arterial hypertension.
Keywords: aldosterone; pulse wave velocity; intima media thickness; hypertension; atherosclerosis; atherosclerotic plaque